Lifeboat 12 - Hood, Susan, 1954- (Simon & Schuster Books for Young Readers, 2018)
In 1940, a group of British children, their escorts, and some sailors struggle to survive in a lifeboat when the ship taking them to safety in Canada is torpedoed. Includes historical notes.